Blood Red Road - Young, Moira (New York : Margaret K. McElderry Books, 2011)
In a distant future, Lugh is kidnapped, and while his twin sister Saba and nine-year-old Emmi are trailing him across bleak Sandsea they are captured, too, and taken to brutal Hopetown, where Saba is forced to be a cage fighter.
Ages 14 up.
Keywords: Kidnapping -- Fiction; Siblings -- Fiction; Twins -- Fiction; Orphans -- Fiction; Science fiction